clinical-ophthalmology 2018
DOI: 10.35841/clinical-ophthalmology.2.1.41-46
|View full text |Cite
|
Sign up to set email alerts
|

Changes of corneal endothelial cell density after EX-PRESS® Glaucoma shunt implantation: 2-year follow-up study.

Abstract: Purpose: To evaluate effects of the EX-PRESS ® glaucoma filtering device on the corneal endothelial cell density (ECD) in eyes with open angle glaucoma (OAG).Designs: A prospective, non-comparative study. Methods: We prospectively evaluated the changes in the ECD, hexagonality, and coefficient of variation (CV) in 20 eyes of 19 patients who had an implantation of the EX-PRESS ® . The type of glaucoma was exfoliation glaucoma in 6 eyes, uveitic glaucoma in 5 eyes, secondary glaucoma following vitrectomy in 4 ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This study revealed early affection of CV% and HEX% but not CEC density, which may be affected in the interval period of chronic IOP elevation before the diagnosis of glaucoma has been made. Yu ZY et al reported that elevated IOP cause destruction of the HEX% and the damage of the cells causes further deformation and loss, but he didn't correlate these changes of corneal endothelial cells to RNFL thickness nor macular GCC thickness 24 Morphological changes of corneal endothelial cell detected in early glaucoma with controlled IOP could be attributed only to IOP changes as eyes with previous surgical and LASER procedures-known to affect corneal endothelium in other studies were excluded [25][26][27] . The effect of topical antiglaucoma medication on corneal endothelium is negligible according to Kwou-Yeung Wu et al, 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed early affection of CV% and HEX% but not CEC density, which may be affected in the interval period of chronic IOP elevation before the diagnosis of glaucoma has been made. Yu ZY et al reported that elevated IOP cause destruction of the HEX% and the damage of the cells causes further deformation and loss, but he didn't correlate these changes of corneal endothelial cells to RNFL thickness nor macular GCC thickness 24 Morphological changes of corneal endothelial cell detected in early glaucoma with controlled IOP could be attributed only to IOP changes as eyes with previous surgical and LASER procedures-known to affect corneal endothelium in other studies were excluded [25][26][27] . The effect of topical antiglaucoma medication on corneal endothelium is negligible according to Kwou-Yeung Wu et al, 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes in CECs detected in early glaucoma with controlled IOP could be attributed only to IOP changes, as eyes with previous surgical and laser procedures known to affect corneal endothelium [ 26 , 27 ] were excluded from our analyses. The effect of topical antiglaucoma medication on corneal endothelium is negligible according to Wu et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed early affection of CV% and HEX% but not CEC density, which occurred in the interval period of chronic IOP elevation before the diagnosis of glaucoma has been made. Yu ZY et al reported that elevated IOP cause destruction of the HEX% and the damage of the cells causes further deformation and loss, but he didn't correlate these changes of corneal endothelial cells to PRNFL thickness nor macular GCC thickness 23 Morphological changes detected in early glaucoma with controlled IOP could be attributed only to IOP changes as eyes with previous surgical and LASER procedures-known to affect corneal endothelium in other studies were excluded [24][25][26] . The effect of topical antiglaucoma medication on corneal endothelium is negligible according to Kwou-Yeung Wu et al, 19 .…”
Section: Discussionmentioning
confidence: 99%